ANALISIS BUTIR SOAL BAHASA ARAB UJIAN AKHIR MADRASAH BERSAMA DAERAH (UAMBD) MADRASAH IBTIDAIYAH TAHUN 2017-2018 - Maulana, Deni; Sanusi, Anwar (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2020)
This study aims to analyze the Arabic question items for the end of the regional joint madrasah (UAMBD) exam for Madrasah Ibtidaiyah (MI) students for the 2017-2018 Academic Year. After conducting research using qualitative descriptive methods with purposive sampling techniques. The result showed that (1) the validity of the contents of the Arabic UAMBD MI Year 2018 shows a very high. This is showed by the level of 100% compatibility of all the items with the specified lattice; (2) UAMBD MI year 2018 Arabic questions have a high level of reliability or consistency, with a test score of 0.68 (at intervals of 0.60-0.80). It can be stated that the use of Arabic in UAMBD in 2018 can be trusted. If the results in terms of difficulties are 63.23% (0.63), it can be said to a standard test; (3) the difference in power shows it is acceptable at 31.4% and acceptable but needs to be improved at 25.7%; and (4) the distribution of 11 question items in Arabic UAMBD MI 2018 has a very good distribution of answer choices (distractors/deceivers); five good questions; six items lacking; nine bad questions; and four items are terrible.